Crafting Labor Policy : Techniques and Lessons from Latin America - Gill, Indermit; Montenegro, Claudio E.; Domeland, Dorte (Washington, DC: World Bank and Oxford University Press, 2013)
Nothing impacts the welfare of individuals and households more directly than employment and earnings opportunities. In developing countries, labor market reform is a crucial component for the success of overall economic policy reforms. Despite success in other areas of economic reform over the past ten years, Argentina, Brazil, and Chile continue to face significant labor policy issues. To reduce the rhetoric around the issues - in Argentina, a high level of unemployment exists; in Brazil, the high costs of public employment have created large government deficits and public debt; and in Chile, there is a growing income inequality and uncertainty of employment - the book uses a systematically quantitative approach. The value of the quantitative methods in analysis is that they can provide frameworks to better understand the effects of various policy actions. The results can then be translated into benefits and costs that policy makers can more easily explain to their constituents. The policy recommendations resulting from the issues analyzed in Crafting Labor Policy: Techniques and Lessons from Latin America may be beneficial to other developing countries enacting labor market reforms.